Indole and bisindole alkaloids from Tabernaemontana corymbosa / Nge Choy Eng - Nge , Choy Eng (2017)
A total of 59 alkaloids (1−59) were isolated and characterized from the leaf and stem-bark extracts of the Malayan Tabernaemontana corymbosa Roxb. ex Wall.. Of these, 25 are new alkaloids. Among the new alkaloids, the pentacyclic alkaloids, voatinggine (1) and tabertinggine (2), which are postulated to derive from a common cleavamine-type precursor, the hexacyclic iboga-derived indole, cononuridine 3, the pentacyclic indoles, criofolinine (4) and vernavosine (5) incorporating pyrroloazepine and pyridopyrimidine moieties, respectively, are notable for incorporating novel or intriguing molecular skeletons. Other new alkaloids isolated from this study include a seco-yohimbine (taberisidine, 7), five iboga (conodusines A−E, 8−12), seven Aspidosperma (apocidines A−G, 20−26), three vincamine (conoduzidines A−C, 30−32), one heteroyohimbine [16α-methoxycarbonyl-16,17-dihydro-19-epi-ajmalicine, 34], two iboga-vobasinyl bisindoles, tabernamidines A and B (55, 56) and one Aspidosperma-Aspidosperma bisindole alkaloid (conofolidine, 59). Two of the iboga alkaloids, conodusines B and C (9, 10) and the iboga containing bisindole (tabernamidine B, 56) are notable for the presence of an α-substituted acetyl group at C-20 of the iboga carbon skeleton (naturally-occurring iboga alkaloids with C-20 substitution by ethyl, hydroxyethyl, or acetyl groups, are usually β-oriented). Conofolidine (59) showed pronounced cytotoxicity toward human KB/S, KB/VJ300(−), KB/VJ300(+), PC-3, LNCaP, MCF7, MDA-MB-231, HT-29, and HCT 116 cancer cells (IC50 0.2−5.9 μg/mL).